Catastrophic cellular events leading to complex chromosomal rearrangements in the germline. Issue 5 (22nd February 2017) - Fukami, M.; Shima, H.; Suzuki, E.; Ogata, T.; Matsubara, K.; Kamimaki, T.
Abstract : Although complex chromosomal rearrangements were thought to reflect the accumulation of DNA damage over time, recent studies have shown that such rearrangements frequently arise from 'all‐at‐once' catastrophic cellular events. These events, designated chromothripsis, chromoanasynthesis, and chromoanagenesis, were first documented in the cancer genome and subsequently observed in the germline. These events likely result from micronucleus‐mediated chromosomal shattering and subsequent random reassembly of DNA fragments, although several other mechanisms have also been proposed. Typically, only one or a few chromosomes of paternal origin are affected per event. These events can produce intrachromosomal deletions, duplications, inversions, and translocations, as well as interchromosomal translocations. Germline complex rearrangements of autosomes often result in developmental delay and dysmorphic features, whereas X chromosomal rearrangements are usually associated with relatively mild clinical manifestations. The concept of these catastrophic events provides novel insights into the etiology of human genomic disorders. This review introduces the molecular characteristics and phenotypic outcomes of catastrophic cellular events in the germline. Abstract :